NOTATIONAL ANALYSIS ON TACTICAL PASSING SKILLS USED BY COLLEGIATE PLAYERS IN AN INDOOR HOCKEY MASUM TOURNAMENT - Mohamad Razali, Abdullah (2018)
The study aimed to determine the relationship of frequency for wall, diagonal and square passing with the performance for men and women team. Eighteen teams (man = 11; woman = 7) involved in this study. The Pearson correlation coefficient was used to examine the relationship between frequency of use wall pass, diagonal pass and square pass with team performance. Results of the study showed a significant relationship between the frequency of the use of passes to the achievement of the team in both categories. The significant value of wall pass, diagonal pass and square pass for men and women teams is (p < 0.05). Positive relationship indicated team that use more wall, diagonal and square passing was a successful team in tournament. The findings for this study could be used by trainers and individuals who involved in the player development and coaches education.